Peripheral Interaction Challenges and Opportunities for HCI in the Periphery of Attention - Bakker, Saskia; Hausen, Doris; Selker, Ted (Human-Computer Interaction Series,, 2016)
Computing devices have become ever more present in our everyday environments, however embedding these technologies into our routines has remained a challenge. This book explores the novel theory of peripheral interaction to rectify this. This theory examines how interactive systems can be developed in such a way to allow people to seamlessly interact with their computer devices, but only focus on them at relevant times, building on the way in which people effortlessly divide their attention over several everyday activities in day to day life. Capturing the current state of the art within the field, this book explores the history and foundational theories of peripheral interaction, discusses novel interactive styles suitable for peripheral interaction, addresses different application domains which can benefit from peripheral interaction and presents visions of how these developments can have a positive impact on our future lives. As such, this book's aim is to contribute to research and practice in fields such as human-computer interaction, ubiquitous computing and Internet of Things, a view on how interactive technology could be redesigned to form a meaningful, yet unobtrusive part of people's everyday lives. Peripheral Interaction will be highly beneficial to researchers and designers alike in areas such as HCI, Ergonomics and Interaction Design.